FAKTOR LINGKUNGAN FISIK YANG BERHUBUNGAN DENGAN INDEKS PINJAL KHUSUS DI WILAYAH FOKUS PES (STUDI DI DUSUN SUROROWO, KABUPATEN PASURUAN TAHUN 2018) - Desy Hafidhotul Ilmi; Retno Hestiningsih; Nissa Kusariana; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2021)
Surorowo hamlet in Kalikebek Village, Tutur Subdistrict, Pasuruan Regency, is one of the focus area of plague that has been monitored by the goverment, as an effort to ensure zero deaths of plague. The monitoring results of the specific flea index in 2017 show a fairly high frequency (≥1), which was obtained by calculating the number of Xenopsylla cheopis per number of trap success. This is an indicator that there is still a risk of plague. The purpose of this study is to analyze the physical environmental factors related to the specific flea index in focus area of plague, Surorowo Hamlet. This type of research is analytic observational research with a cross sectional approach. The population in this study were 60 houses that had traps installed by Zoonosis Laboratory field officers to monitor trap success and flea index in the house. The sampling technique used total sampling so that the number of samples was the same as the population, as many as 60 houses. The results showed that there are 4 physical enviromental variables related to the specific flea index, namely the type of house walls (p=0,0), the existance of windows (p=0,0), the existance of ceiling (p=0,0), and the temperature level (p=0,01). Based on the results of this study, to reduce the risk of the high specific flea index in Surorowo Hamlet, the community need to reduce the cavities in the walls that can be a place to live and a path for rats. In addition, it is necessary to procure windows to ensure good lighting and humidity in the house, and reducing wooden dividers on the ceiling of the house so that it does not become a path for rats.